INFLATION AND PRODUCTION COSTS OF SELECTED AGRICULTURAL PRODUCTS IN POLAND IN 2022 - Marian Podstawka (Polityki Europejskie, Finanse i Marketing)
The aim of the paper is to present measures taken in recent years by state public authorities that affect inflation in Poland. An assessment was made of the growth in prices for purchased agricultural inputs, which was correlated with cost structures, and on this basis an increase in the production costs of basic agricultural products in 2022 was estimated. This projected increase in production costs was then related to estimated income. This made it possible to determine their growth, which would allow the current level of agricultural income to be maintained. The government rescue measures triggered by COVID-19 had three main sources of funding: expenditure of the state budget and the budget of European funds - PLN 23.2 billion, COVID-19 Counteracting Fund - PLN 92.7 billion, and financial shields of the Polish Development Fund - PLN 63.5 billion, While the government's intervention activities, under the conditions of the crisis, should be assessed positively, their methods of implementation should be assessed critically. Financial support under the shields was given to companies that showed a decline in turnover caused by the coronavirus pandemic. As a result, those companies that may have deliberately created the conditions to receive support were supported. In all analyzed types of agricultural crop production activities in 2022, there will be an increase in the cost of their production by about 50-60%. The exception will be the production of rye, where the cost increase will be even higher.